SIFAT PAPAN BLOK DENGAN INTI LIMBAH EKSPLOITASI HUTAN LAMPUNG - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Blockboards of six wood species of logging waste from Lampung as core strip material were manufactured in the laboratory, and their physical and mechanical properties were tested.The average value of moisture content, board density and strip density were 10.09%, 0.63 g/cm3 and 0.49 g/cm3, respectively. Bending strength parallel to the grain varied between 690.47 kg/cm2 (red meranti) and 1041.99 kg/cm2 (keruing). The bending strength perpendicular to the grain varied between 112.40 kglcm2 (Bima) and 319.90 kg/cm2 (Pulai), and bending strength parallel to the grain were significantly affected by wood species, but bending strength perpendicular to the grain were not.